Experience tourism: development possibilities in the Bioceanic Corridor - Fittipaldi Gonçalves, Débora (2021)
The tourism sector is one of the most powerful generators of economic growth, employment, added value, and services export in the world. In this context, the objective of this article is to discuss tourism and experience tourism possibilities in the region that the Bioceanic Corridor will traverse from the Latin American Integration Route (RILA), involving Brazil, Paraguay, Argentine, and reaching Northern Chile in Antofagasta and Iquique. Regarding methodology, it uses the deductive method and is based on bibliographic and documentary research with access to the articles, indicators, and documents needed. In this regard, regional development issues are presented, followed by experience tourism as a possibility for development, and finally, some indicators and data about tourism are analyzed, seeking an interface with the Bioceanic Corridor. After analyses, it is pointed out that tourism has become one of the fundamental factors for territorial development, presenting new and other values and meanings to the territory, as well as a production resource, discovering another perspective when interpreting rural and natural spaces. Thus, it arises as a new alternative to globalization and, in this context, experience tourism gains prominence considering the significant increase of tourism in the world in 2010, and perspectives until 2030. It is inferred, therefore, that RILA is a great window of opportunity for socioeconomic development through tourism and more specifically experience tourism.